Development of creative thinking skills through STEM-based instruction in senior high school student. (June 2020) - Iskandar,; Sastradika, D; Jumadi,; Pujianto,; Defrianti, Denny
Abstract: Creative thinking is one of the abilities in the 21st Century that must be mastered by students. The difficulty of developing students' creative thinking is because teachers in the school do not make a collaboration between technology and science in learning. The purpose of this study is to develop creative thinking through the application of Science Technology Engineering and Mathematics (STEM) based learning. This research was conducted at 1 Kerinci Public High School. the sample include 90 Students divided into three classes namely Experiment Class 1 (EC1) are given STEM-based learning, experiment Class 2 (EC 2) given Science Engineering Mathematics Learning (SEM) and Control Class (CC) given conventional learning. The method used is a quasi-experiment with pre-post control design. The instrument used was 12 essay questions validated by 7 experts. The results were analysis using Anava mixed method with the General Linear Model. The results show that STEM-based learning improves creative thinking skills by 0.663 or 66.3% in the medium category, this shows that STEM-based learning is effective in developing students' creative thinking, STEM-based learning also provides experience to students in collaborating between technological science, engineering and mathematics in optimizing learning.